H-intensity scale score to estimate CSF GluN1 antibody titers with one-time immunostaining using a commercial assay - Iizuka, Masaki; Nagata, Naomi; Kanazawa, Naomi; Iwami, Tomomi; Nagashima, Makoto; Nakamura, Masaaki; Kaneko, Juntaro; Kitamura, Eiji; Nishiyama, Kazutoshi; Mamorita, Noritaka; Iizuka, Takahiro (Frontiers in Immunology, 2024)
Introduction: Anti-NMDA receptor encephalitis is an autoimmune disorder caused by autoantibodies (abs) against the conformational epitope on GluN1 subunits. GluN1-abs have been determined with cell-based assay (CBA) co-expressing GluN1/GluN2 subunits. However, commercial fixed CBA expressing only GluN1 subunit has increasingly been used in clinical practice. Ab titers can be determined with serial dilutions but its clinical significance remains unclear. We aimed to develop an H-Intensity Scale [HIS] score to estimate GluN1-ab titers in cerebrospinal fluid (CSF) with one-time immunostaining using both commercial CBA and immunohistochemistry, and report its usefulness. The “H” is the initial of a patient with high CSF GluN1-ab titers (1:2,048). Methods: We first determined the reliability of CBA in 370 patients with suspected autoimmune encephalitis by comparing the results between commercial CBA and established assay in Dalmau's Lab. Then, we made positive control panels using the patient H’s CSF diluted in a 4-fold serial dilution method (1:2, 1:8, 1:32, 1:128, 1:512, and 1:2,048). Based on the panels, we scored the intensity of ab reactivity of 79 GluN1-ab-positive patients' CSF (diluted at 1:2) on a scale from 0-6 (with ≥ 1 considered positive). To assess inter-assay reliability, we performed immunostaining twice in 21 patients' CSF. We investigated an association between the score of CSF obtained at diagnosis and clinical/paraclinical features. Results: The sensitivity and specificity of CBA were 93.7% (95% CI 86.0-97.3) and 98.6% (95% CI 96.5-99.5), respectively. Linear regression analysis showed a good agreement between the scores of the first and second assays. Patients with a typical spectrum, need for mechanical ventilation support, autonomic symptoms/central hypoventilation, dyskinesias, speech dysfunction, decreased level of consciousness, preceding headache, ovarian teratoma, and CSF leukocyte count > 20 cells/µL had higher median HIS score than those without, but HIS score was not associated with sex, age at onset, or seizure. HIS score at diagnosis had a significant effect on one-year functional status. Discussion: The severity of disease and four core symptoms were associated with higher GluN1-ab titers in CSF at diagnosis, which may play a role on poor one-year functional status. An incomplete phenotype can be attributed to low CSF GluN1-ab titers.